Brazil’s quest for autonomy in Asia: the role of strategic partnerships with China and Japan - Amorim,Samuel Conde (2021)
Abstract This article aims at examining the strategic partnerships Brazil developed with China and Japan, between 2003 and 2020, and assessing how these privileged rapports contributed to the country’s quest for autonomy. This will be made through the lenses of Pragmatic Institutionalism and against the backdrop of major developments in global and regional governance that impacted on the Brazilian autonomist project.